Florida's Native Bromeliads - Barbra C. Larson; J. Howard Frank; Ginger M. Allen; Martin B. Main (EDIS)
Bromeliads are members of the pineapple family Bromeliaceae. They are perennial herbs that lack woody stems and typically grow on other plants or substrates. Bromeliads are not mosses as some of their common names suggest. They are flowering plants, although their blossoms can be very small. This document is CIR 1466, one of a series of the Wildlife Ecology and Conservation Department, UF/IFAS Extension. Original publication date September 2004.